Preparation and Physico-Chemical Properties Evaluation of Biodiesel from Pithraj (Aphanamixis Polystachya)Seeds available in Bangladesh (Chemical Engineering Research Bulletin, 2021)
In this study, Pithraj (Aphanamixis polystachya) seed (PS) oil was used to produce biodiesel via trans-esterification process. The PS oil was extracted from seed using a soxhlet solvent extraction technique and the effect of temperature and heating rate on product distribution was investigated. The PS oil was pretreated (esterified) to combat the saponification reaction and other associated problems e.g., phase separation. The transesterification reactions were carried out and the optimum biodiesel yield was found 93.87%, when the reaction condition was as follows: addition of 50 wt.% methanol, 0.8 wt.% NaOH (both are on the basis of wt.% of PS oil addition), 60 °C reaction temperature and 90 min reaction time. Biodiesel produced from PS oil was characterized by various physico-chemical means and compared with international standards. The use of the produced biodiesel in blend with commercial diesel will bring a remarkable change in fuel economy of the country, will ensure a clean and safe environment and will demonstrate a way for ‘Waste to Energy’.Chemical Engineering Research Bulletin 21(2020) 43-48